RESPON PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum) TERHADAP PEMBERIAN ZAT PENGATUR TUMBUH DAN PUPUK NPK PADA TANAH SPODOSOL (The Growth and Yield Response of Onion (Allium ascalonicum)of Giving The Plant Growth Regulators (PGR) and NPK Fertili: Saputra, W.L.A1), Lautt, B.S. 1) , Asie, E.R. 1), dan Nyahu 1), - journal journal (AgriPeat, 2017)
ABSTRACT The purpose of this study was to determine the growth and yield of onion that were given growth regulator (PGR) and NPK fertilizer on spodosol. This study used Randomized Block Design (RBD) of factorial pattern with two factors: (1) growth regulator (0, 3, 6, and 9 mL.L-1 ), and (2) NPK fertilizer (0, 150, 300, and 450 kg ha-1). The results of this study showed tha giving of PGR increased the crop growth rate of plants aged 14-21 day after planting (1.057 g.m-2 day -1) and 21-28 day after planting (1.089 g.m-2 day-1) with the best concentration of 6 mL.L-1 water. The best NPK fertilizer dosage of 300 kg.ha-1 was able to increase plant height at 42 day after planting (46,89 cm), leaf area 21, 28 and 35 day after planting (541,22 cm2, 717,37 cm2, and 714 , 29 cm2), weight of fresh stover (75,50 g), weight of dry stover (66,19 g) and tuber weight per plot (4,520,25 g). Key words : onion, plant growth regulator (PGR), NPK, spodosol ABSTRAK Tujuan penelitian untuk mengetahui pertumbuhan dan hasil tanaman bawang merah yang diberi zat pengatur tumbuh (ZPT) dan pupuk NPK pada tanah spodosol. Penelitian ini menggunakan menggunakan Rancangan Acak Kelompok (RAK) pola faktorial dengan dua faktor, yaitu : (1) zat pengatur tumbuh (0, 3, 6, dan 9 mL.L-1 air), dan (2) pupuk NPK ( 0, 150, 300, dan 450 kg.ha-1). Hasil penelitian menunjukkan bahwa pemberian ZPT meningkatkan laju pertumbuhan tanaman umur 14-21 hst (1,057 g.m-2. hari -1) dan 21-28 hst (1,089 g.m-2. hari -1) dengan konsentrasi terbaik 6 mL.L-1 air. Dosis pupuk NPK terbaik 300 kg.ha-1 mampu meningkatkan luas daun umur 21, 28 dan 35 hst, masing-masing 541,22 cm2, 717,37 cm2, dan 714,29 cm2, bobot brangkasan segar (75,50 g), bobot brangkasan kering (66,19 g) dan bobot umbi per petak (4.520,25 g). kata kunci: bawang merah, zat pengatur tumbuh (ZPT), NPK, spodosol